Counseling PENYULUHAN DAN EDUKASI PENYAKIT INFEKSIUS HIV/AIDS DI STIT DARUL FATAH BANDAR LAMPUNG - HARTANTI -; Wimba Widaghdo Dinutanayo; A. Zakaria Amien; Rodhiansyah Djayasinga (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
The behavior of adolescents in preventing HIV/AIDS will be greatly influenced by their knowledge and attitudes towards HIV/AIDS. Following up on this, it is necessary to carry out efforts to increase youth knowledge about HIV/AIDS through outreach activities. It is hoped that this outreach and education activity will improve attitudes and behavior in preventing the transmission of HIV/AIDS. The purpose of this activity is to carry out outreach and education regarding HIV/AIDS infectious diseases to students of STIT Darul Fatah, Bandar Lampung as an effort to prevent infection and transmission of HIV/AIDS. This activity is carried out using counseling, education, and discussion methods about understanding, ways of transmission, ways of prevention, examination, treatment and care of people living with HIV/AIDS (PLWHA). The implementation time is Thursday, June 9 2022, at the STIT Darul Fatah Campus, Jl. Coffee No. 23A, Meneng Building, Bandar Lampung. The activity was attended by 30 semester 2 students. Outcome evaluation of the activity was carried out by administering a pre-test and post-test in the form of a questionnaire about HIV/AIDS. The results of the questionnaire showed that there was an increase in knowledge about HIV and AIDS from the results of the pre-test and post-test given before and after the counseling was carried out. This shows that counseling activities are effective in increasing students' knowledge about HIV and AIDS